An Intuitive Method to Solve Quadratic Equations. (1st January 2023) - Missa, Abdel
Summary: This article provides an intuitive, simple and computationally efficient method to solve for general quadratic equations compared to the traditional completing the square method. The only basic knowledge required for this purpose is the factoring/distributive property. Therefore, students can learn how to solve quadratic equations at an earlier stage without the need to memorize a formula.